2015
DOI: 10.4025/actascitechnol.v37i4.27855
|View full text |Cite
|
Sign up to set email alerts
|

<b>Parameterization effects in nonlinear models to describe growth curves

Abstract: Various parameterizations of nonlinear models are common in the literature.In addition to complicating the understanding of these models, these parameterizations affect the nonlinearity measures and subsequently the inferences about the parameters. Bates and Watts (1980) quantified model nonlinearity using the geometric concept of curvature. Here we aimed to evaluate the three most common parameterizations of the Logistic and Gompertz nonlinear models with a focus on their nonlinearity and how this might affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 18 publications
(4 reference statements)
0
35
0
10
Order By: Relevance
“…For the evaluators, residual standard deviation (DPR) and Akaike's information criterion (AIC), the logistic model revealed lower values, suggesting a better fit; also, according to the findings of FERNANDES et al, (2015) the lower AIC values suggested that this model best describes the data. Therefore, the adjustment quality evaluators highlight the superiority of the Logistic model with second order autoregressive errors to describe the pear fruit length increase.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For the evaluators, residual standard deviation (DPR) and Akaike's information criterion (AIC), the logistic model revealed lower values, suggesting a better fit; also, according to the findings of FERNANDES et al, (2015) the lower AIC values suggested that this model best describes the data. Therefore, the adjustment quality evaluators highlight the superiority of the Logistic model with second order autoregressive errors to describe the pear fruit length increase.…”
Section: Resultsmentioning
confidence: 94%
“…The Gompertz and Logistic growth models were effective in describing the cacao fruit development , and the fruits of the cashew tree (MUIANGA et al, 2016), dopequi (FERNANDES et al, 2015), and coffee tree (FERNANDES et al, 2014), giving satisfactory results, for all instances. JESUS et al, (2008) in their study of the longan fruit growth, did a comparison of the Logistic and Quadratic Exponential models and observed that the Logistic model fitted better.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear models have been used in plant science studies with satisfactory results, which allowed to estimate fruit growth parameters with biological interpretation, for example, on dwarf date palm (TERRA; SAVIAN; MUNIZ, 2010), dwarf green coconut (PRADO; SAVIAN; MUNIZ, 2013), the Cerrado pequi (FERNANDES et al, 2015) and cashew (MUIANGA et al, 2016). These models were also used in the description of the germination curve of seeds (SOUSA et al, 2014), plant growth (PEREIRA et al, 2014) and canopy diameter (WYZYKOWSKI et al, 2015) of coffee plants.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the residual standard deviation (RSD) and corrected Akaike information criterion (AIC), the Gompertz model presented lower values and according to results obtained by Fernandes et al (2015), the lower AIC and RSD values suggest that the model best describes data. Therefore, adjustment quality evaluators point out superiority of the Gompertz model to describe the crosssectional growth of pequi fruits.…”
Section: Resultsmentioning
confidence: 88%
“…Considering the adjustment of nonlinear models, the estimation of parameters from the classical point of view is usually performed based on the minimization of the sum of squares of residuals, which leads to a system of normal equations with no analytical solution, so iterative processes should be used to obtain estimates (DRAPER, SMITH, 1998;SOUZA, 2007). Several iterative methods are used, especially Gauss-Newton (PEREIRA et al, 2005;MENDES et al, 2008;ZEVIANI et al, 2012;CARNEIRO et al, 2014;FERNANDES at al., 2015). In regression studies, it is usual to admit in the estimation process and inference under parameters that the errors are independent, which does not necessarily occur when working with time-ordered data that are potentially correlated (CASSIANO; SÁFADI, 2015).…”
Section: Introductionmentioning
confidence: 99%